Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Bradynobaenidae - Gadallah, Neveen S.; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Bradynobaenidae is provided here. The list includes 40 identified species in four genera and one subfamily: Apterogyninae (Apterogyna, 9 species; Gynecaptera, 1 species; Macroocula, 24 species; Micatagla, 6 species). Distributions, both on the Peninsula and extra-limital, are provided for each species and subspecies; 29 species (73%) are endemic to the Arabian Peninsula.